Planejamento estatístico de experimentos como uma ferramenta para otimização das condições de biossorção de Cu(II) em batelada utilizando-se casca de nozes pecã como biossorvente Statistical design of experiments as a tool for optimizing the batch conditions of Cu(II) biosorption using pecan nutshells as biosorbent - Jorge L. Brasil (Química Nova, 2007)
In order to reduce the total number of experiments for achieving the highest amount of adsorbed Cu2+ (qmax) using pecan nutshells (Carya illinoensis) as biosorbent, a full 2(4) factorial design with two central points was carried out (mass of biosorbent- m, pH, initial metallic ion concentration- C0, time of contact- t). In order to continue the optimization of the system, a central composite surface analysis design with two factors and five central points was carried out. The maximum amount of Cu2+ taken up by the pecan nutshells was 20 mg g-1. These results were confirmed by determining a Cu2+ isotherm using the best conditions attained by the statistical design of experiments.